Fabrication and Characterization of Photodiode Flame Distance Sensor - Asep Ridwan Nugraha; Andri Rahmadhani (LIPI Press, Anggota IKAPI, 2015)
The ﬂame distance sensor is designed to use when open ﬂaming fres occur. It responds to the light emitted by ﬂame during combustion. The detector discriminates between ﬂame and other light sources by responding only to particular optical wavelengths. The physical quantity that can be used as a reference for determining the distance of the ﬂame is the intensity of radiation emitted by the ﬂame. Intensity of radiation can be measured by the photodiode output, when the photodiode receives the radiation. In this research, the writers propose to develop a new prototype of simple, low-cost ﬂame sensing device using a photodiode. The photodiode is integrated with an infrared flter, which is made of black flm inside the ﬂoppy disk, to block certain wavelengths other than infrared. The photodiode is operated in photoconductive mode, where a positive regulated DC power supply is connected to the cathode. The anode is connected to the output terminal and a resistor that acts as a voltage divider. The voltage will be changed at the output terminal as the photodiode receives different intensity of radiation. The relationship between output voltage and intensity can be obtained and verifed by using a calibrated lux meter. The radiation intensity is inversely proportional to the square of the distance from the radiation source. Given this relationship, the distance can be calculated with a ﬂame coming from the photodiode output. As the result, the maximum detection distance and intensity of the sensor is 107 cm and 1783 lux.Keywords: characterization, flter, ﬂame distance, infrared, photodiode, sensor